Effect of Herbal Galactogogue (Sanjivani biokseera) on Milk Yield and Milk Constituents in Lactating Kankrej Cattle at Organised Farm - Panchasara, HH; Chaudhari, AB; Patel, DA; Gami, YM; Patel, MP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was conducted to evaluate the effect of feeding herbal galactogogue preparation (Sanjivani biokseera) on the milk yield and milk constituents in lactating Kankrej cows. Thirty-two lactating Kankrej cows in their 1st to 6th lactation were taken for the experiment from 3 days after calving up to 52 days postpartum. All the animals were fed as per the standard seasonally available roughages and concentrates to meet their nutritional requirements. The cows were randomly divided into two uniform groups of 16 cows in each according to initial milk yield and milk composition. The animals in group-I were not given any supplement and served as control. The animals in group-II were given Sanjivani biokseera (Naturewell Industries) @ 60 g per day for 1-month, commencing 3 days after calving, in addition to the usual feeds/fodders. A clear difference was observed in milk yield from day 8 onward of experiment between groups with significant (p <0.05) higher values from day 16–52 in cows fed herbal galactogogue as compared to control, but no such distinct effect on milk constituents was observed on day 52 when analyzed. The use of herbal galactogogue significantly (p <0.05) increased the overall average of 52 days milk production, which was 9.34 ± 0.21 lit/day in supplemented as compared to 7.75 ± 0.26 lit/day in control animals. It was concluded that herbal galactogogue (Sanjivani biokseera) could increase milk yield in lactating dairy cows through its galactopoetic property and improved rumen environment.